Cytologic features of angiolymphoid hyperplasia with eosinophilia: Highlighting the diagnostic clues. Issue 1 (4th August 2020) - Velamala, Pavani; Gupta, Parikshaa; Gupta, Nalini; Radotra, Bishan Dass; Rajwanshi, Arvind
Abstract: Angiolymphoid hyperplasia with eosinophilia (ALHE) is an uncommon, benign, inflammatory disorder involving the skin and microvasculature with an undetermined etiopathogenesis. Although the histopathology is well‐characterized, the cytologic features of this entity have been rarely described in literature. This study was conducted to describe in detail the cytomorphologic features of ALHE and to identify the characteristic features that can help in establishing a correct diagnosis of this entity. This was a retrospective study conducted over a period of 3 years, wherein the corresponding cytologic smears of histopathologically diagnosed cases of ALHE were retrieved and reviewed. All the cytologic features were recorded to identify characteristic features that can be used to differentiate ALHE from other cytologic mimics. On histopathologic examination, 15 cases were reported as ALHE. Corresponding cytologic samples were available for three cases. All the three cases were males who were 21, 22 and 52 years old, respectively. The sites of the swellings were scalp, orbital and preauricular. The most consistent cytologic findings were the presence of eosinophilia, scattered plump endothelial cells and a reactive lymphoid background. We believe that a thorough cytologic examination for the presence of plump to spindle‐shaped cells in smears with eosinophilia and reactive lymphoid tissue, can help in reaching to a cytologic diagnosis of ALHE in suspected cases.